Pengaruh Tekanan Stakeholder dan Ukuran Perusahaan terhadap Sustainability Report Assurance: Studi Empiris pada Perusahaan Terdaftar di Bursa Efek Indonesia Periode Tahun 2017-2021 - Rezza Alfajar; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to analyze the effect of environmental pressure, employee pressure, government pressure, and company size on sustainability report assurance in companies listed on the Indonesian Stock Exchange (BEI) for the 2017-2021 period. The dependent variable in this study is sustainability report assurance which is measurement using dummy variables which are divided into 2 categories. While the independent variables in this study consists of 4 variables, namely the first is environmental pressure with its measurement using a dummy variable which is divided into 2 categories, the second is employee pressure with its measurement using the natural logarithm (Ln) of the number of employees, the third is government pressure with the measurement uses a dummy variable which is divided into 2 categories, and the fourth is company size with its measurement using the natural logarithm (Ln) of total assets. This Research is a quantitative research. The research data used is Secondary data obtained from the IDX and the official websites of each company. The selection of research samples was carried out using purposive sampling technique and obtained a sample of 51 companies with a total of 255 objects of observation. The analysis technique used is binary logistic regression analysis. The research results that environmental pressure and employee pressure have a positive effect on sustainability report assurance, while government pressure and company size have a negative effect on sustainability report assurance.